2013
DOI: 10.1021/la400082z
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Dynamics and Energy Landscape of Decanethiolates in Self-Assembled Monolayers on Au(111) Studied by Scanning Tunneling Microscopy

Abstract: The energetics and dynamics of the various phases of decanethiolate self-assembled monolayers on Au(111) surfaces were studied with scanning tunneling microscopy. We have observed five different phases of the decanethiolate monolayer on Au(111): four ordered phases (β, δ, χ*, and φ) and one disordered phase (ε). We have determined the boundary free energies between the disordered and order phases by analyzing the thermally induced meandering of the domain boundaries. On the basis of these results, we are able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 40 publications
3
45
1
Order By: Relevance
“…Although, we are the first to introduce the idea of the double deck packing of alkyl chain at physisorbed interface, at chemisorbed interfaces, similar double-deck packing has already been proposed. [2][3][4][5][6][7][8][9][10][11][12][13] . For the SAM δ phase besides the well known 'standing up' phase (φ) of alkanethiol SAMs at higher coverage, there is a stacked-lying down phase (δ) and an unstacked-lying down phase (β) existing at intermediate and low surface coverage, respectively.…”
Section: Section 3 Double Deck Packing At Chemisorbed Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, we are the first to introduce the idea of the double deck packing of alkyl chain at physisorbed interface, at chemisorbed interfaces, similar double-deck packing has already been proposed. [2][3][4][5][6][7][8][9][10][11][12][13] . For the SAM δ phase besides the well known 'standing up' phase (φ) of alkanethiol SAMs at higher coverage, there is a stacked-lying down phase (δ) and an unstacked-lying down phase (β) existing at intermediate and low surface coverage, respectively.…”
Section: Section 3 Double Deck Packing At Chemisorbed Interfacesmentioning
confidence: 99%
“…[10] Sotthewes et al found the depth of the troughs to be about twice the height for the β phase in comparison to the δ phase. [12] Wu et al studied the dynamics of decanethiol self-assembled monolayers on Au and discovered that the δ phase has much lower dynamics than the β phase. They believe that the alkyl chains in the δ phase experience an even larger van der Waals interaction as compared to the alkyl chains in the β phase.…”
Section: Section 3 Double Deck Packing At Chemisorbed Interfacesmentioning
confidence: 99%
“…Among SAMs, the better known are those formed by thiols and dithiols on different oxide-free metals [18][19][20] and on semiconductors [21,22]. They have been studied by many different and complementary techniques, where scanning probes microscopies are the most used evidences [23,24]. Moreover, these techniques are usually complemented by different electron spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, scanning tunneling microscopy (STM) images of these samples show atomic flat areas on top of the Au(111) surface which are compatible with a self-assembled monolayer [27,28]. From a theoretical point of view, some attempts have been performed under the frame of molecular dynamics [23,29,30], however this approach has two important limitations: an empirically adjusted force field is needed for each interatomic interaction, and computer simulations cannot be performed at low and intermediate molecule concentrations [31]. However, we should point out that very recently a new approach has been proposed which could reduce the effects of this limitation [32].…”
Section: Introductionmentioning
confidence: 99%
“…Better contacts will in turn aid the development of materials that provide selfassembled, stable molecular tunnel junctions. Atomic resolution scanning tunnelling microscopy (STM) data of surface migration and reconstructions is rare but becoming more available for metals and metal oxides; see, e.g., the alkanethiolate-Au (111) surface structure resolved in ref 14 and oxygen defect dynamics in manganite monitored as described in ref 15 .…”
Section: Introductionmentioning
confidence: 99%